The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1023/a:1008996908797
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Diopside was prepared by sintering a powder compact of composition CaO-MgO-2SiO2 at 1300 degreesC for 2 h. The bending strength of diopside was 300 MPa and the fracture toughness was 3.5 MPa m1/2. It was proved that diopside has no general toxicity in cell culture. Diopside implanted in rabbits came in close contact with the newly grown bone. X-ray microanalysis spectral diagrams show a change of composition across the junction from the diopside to the newly grown bone. High-resolution transmission electron mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(48 citation statements)
references
References 7 publications
1
37
0
Order By: Relevance
“…The combination of glass-based ceramics with TCP may lead to novel bioactive and bioresorbable materials for bone regeneration. It has been reported that diopside (CaO$MgO$2SiO 2 ) ceramics show potential for making direct contact with bone, and they show high mechanical strength (Nonami & Tsutsumi 1999). Glass-ceramics containing TCP and diopside would therefore be candidate materials for showing high bioactivity and high mechanical strength in the initial stages after implantation, followed by appropriate degradation during bone regeneration.…”
Section: Glass-ceramics In Thementioning
confidence: 99%
“…The combination of glass-based ceramics with TCP may lead to novel bioactive and bioresorbable materials for bone regeneration. It has been reported that diopside (CaO$MgO$2SiO 2 ) ceramics show potential for making direct contact with bone, and they show high mechanical strength (Nonami & Tsutsumi 1999). Glass-ceramics containing TCP and diopside would therefore be candidate materials for showing high bioactivity and high mechanical strength in the initial stages after implantation, followed by appropriate degradation during bone regeneration.…”
Section: Glass-ceramics In Thementioning
confidence: 99%
“…Forsterite (Mg 2 SiO 4 ) is an important material of olivine family of crystals in the magnesia-silica system. Recently researches have shown that it is a biocompatible material, possess excellent in vitro apatite-formation ability, in vivo bioactivity and degradability [23][24][25][26][27][28][29], improved mechanical properties compared to hydroxyapatite [28], and can be useful as a biomaterial * Corresponding author. [23,30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Kokubo et al [258,259] and Ohtsuki et al [260] showed that the CaO-SiO 2 components contributed mainly to the bioactivity of the CaOÁSiO 2 -based glass and ceramics. De Aza et al [261][262][263][264] pointed out that wollastonite ceramics (CaSiO 3 ) were bioactive and Nonami and Tsutsumi [265] working with diopside (CaO-MgO-2SiO 2 ) ceramics found that an apatite layer was formed on the surface of diopside ceramics implanted into the bone of rabbits and monkeys. However, clinical applications have been sparse on account of their relatively poor mechanical properties.…”
mentioning
confidence: 99%